Electrosynthesized polypyrrole/zeolite composites as solid contact in potassium ion-selective electrode. (20th February 2017) - Yu, Kai; He, Ning; Kumar, Narendra; Wang, NianXing; Bobacka, Johan; Ivaska, Ari
Highlights: Polypyrrole/zeolite composites were prepared electrochemically. The composites were used as solid contact in K + -ISEs. The Si/Al ratio of the zeolite was found to influence the electrode performance. The detection limit of the K + -ISEs was enhanced by long-time conditioning. Abstract: Polypyrrole/zeolite composites were studied as solid contact material in potassium ion-selective electrodes (K + -ISEs). Proton-exchanged Zeolite Socony Mobil-5 (H-ZSM-5) with SiO2 /Al2 O3 ratios of 23, 80 and 280 were electrochemically synthesized with polypyrrole (PPy). The anionic groups on the zeolite framework functioned as the counter ions for PPy during the reaction. H-ZSM-5 particles were observed on the surface as well as inside the composite films. PPy/H-ZSM-5 composites gave a similar cyclic voltammogram as PPy doped with chloride, PPy(Cl − ). The hydrophobicity of the composites decreased in the order PPy/H-ZSM-5–23 > PPy/H-ZSM-5–80 > PPy/H-ZSM-5-280. The redox capacitance of the composite was better utilized than that of PPy(Cl − ) after they were coated with a plasticized PVC membrane. PPy/H-ZSM-5 composite-based K + -ISEs exhibited similar potential stability as the PPy(Cl − )-based K + -ISE. However, when compared with the PPy(Cl − )-based K + -ISE, the detection limit of PPy/H-ZSM-5 composite-based K + -ISEs was enhanced after a long-term conditioning.